Cooperative control of blood compatibility and re-endothelialization by immobilized heparin and substrate topography - Ding, Yonghui; Yang, Meng; Yang, Zhilu; Luo, Rifang; Lu, Xiong; Huang, Nan; Huang, Pingbo; Leng, Yang (Acta biomaterialia, 2015)
[Display omitted] A wide variety of environmental cues provided by the extracellular matrix, including biophysical and biochemical cues, are responsible for vascular cell behavior and function. In particular, substrate topography and surface chemistry have been shown to regulate blood and vascular compatibility individually. The combined impact of chemical and topographic cues on blood and vascular compatibility, and the interplay between these two types of cues, are subjects that are currently being explored. In the present study, a facile polydopamine-mediated approach is introduced for immobilization of heparin on topographically patterned substrates, and the combined effects of these cues on blood compatibility and re-endothelialization are systematically investigated. The results show that immobilized heparin and substrate topography cooperatively modulate anti-coagulation activity, endothelial cell (EC) attachment, proliferation, focal adhesion formation and endothelial marker expression. Meanwhile, the substrate topography is the primary determinant of cell alignment and elongation, driving in vivo-like endothelial organization. Importantly, combining immobilized heparin with substrate topography empowers substantially greater competitive ability of ECs over smooth muscle cells than each cue individually. Moreover, a model is proposed to elucidate the cooperative interplay between immobilized heparin and substrate topography in regulating cell behavior.